2021
DOI: 10.1038/s41586-021-03187-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of TFH selection during the germinal centre reaction

Abstract: Summary The germinal center is a dynamic microenvironment wherein B cells expressing high affinity antibody variants produced by somatic hypermutation are selected for clonal expansion by limiting numbers of T follicular helper cells 1 , 2 . Although much is known about the mechanisms that control B cell selection in the germinal center, far less is understood about the clonal behavior of the T follicular helper cells that regulate this process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 36 publications
(51 reference statements)
5
73
2
Order By: Relevance
“…Naive B cells and Tfh cells interact using a variety of signals, including MHC-II:TCR, CD40/CD40L, ICOS/ICOSL, SAP/SLAM and various cytokine signals which activate the B cell ( Figure 2B ). 73 , 86
Figure 2 Simplified pathway of MBC differentiation. ( A ) Naive B cells capture antigen from subcapsular macrophages, which initiates differentiation.
…”
Section: Generation Of Allergen-specific Memory B Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Naive B cells and Tfh cells interact using a variety of signals, including MHC-II:TCR, CD40/CD40L, ICOS/ICOSL, SAP/SLAM and various cytokine signals which activate the B cell ( Figure 2B ). 73 , 86
Figure 2 Simplified pathway of MBC differentiation. ( A ) Naive B cells capture antigen from subcapsular macrophages, which initiates differentiation.
…”
Section: Generation Of Allergen-specific Memory B Cellsmentioning
confidence: 99%
“…[69][70][71][72] Tfh cell maturation evolves via interactions with antigen-primed B cells at the T-B border. 72,73 Here, ICOS/ICOSL and CD40/CD40L costimulation and Tfhderived IL-21 retain the Tfh phenotype and allow these cells to penetrate the B-cell follicle to join or initiate GCs. 52,71 It is within the GC that the newly identified Tfh13 population has been reported, but it is unknown at what point these cells https://doi.org/10.2147/ITT.S284823…”
Section: Generation Of Allergen-specific Memory T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the repertoire and specificity of Tfh cells might be critical in determining the GC longevity. Recent findings suggested that the Tfh cells undergo selection similar to GC B cells ( 106 ). In this process, Tfh cells with high affinities towards the pMHC presented by B cells are selected ( 106 ).…”
Section: Progressive Changes In T Follicular Helper Cellsmentioning
confidence: 99%